Validation of scale of changes in lifestyles during the quarantine period in a population of university students from Lima, Peru: Validación de escala de cambios en los estilos de vida durante el periodo de cuarentena en una población de estudiantes universitarios de Lima, Perú - Vera-Ponce, Víctor Juan (2020)
Introduction: Due to the presence of Covid-19 in the world, several countries, including Peru, have taken measures, including compulsory social isolation (quarantine). The inability of people to carry out their daily activities has directly affected their lifestyles. A population quite susceptible to these changes are university students. Objectives: To develop a validation scale to know what are the changes in lifestyles during the quarantine period in a population of university students from Lima, Peru. Results: The final scale was made up of 25 items. Bartlett's sphericity test was significant (3514.19, gl = 300, p <0.001) and the Kaiser-Meyer-Olkin sample size adequacy indicator was adequate (0.845). The four thematic areas were changes with respect to 1) Eating habits; 2) Harmful habits; 3) Physical activity; and 4) Use of communication media. As it was a Likert-type ordinal measurement scale, the results were confirmed through the Factor Analysys program, obtaining a KMO of 0.80 (reliable) and the significant Bartlett sphericity test (5528.8; p <0.001; gl = 300). confirming the existence of 7 components that explain 63% of the variance. Conclusions: This scale gathers the psychometric properties to be considered a useful, valid and reliable instrument to measure these changes in students of health science careers, being necessary to validate it prospectively in other careers and countries.